The evaluation of the Cultural Journeys in the Information Society environment as an educational aid - Fakas, Georgios; Schizas, Christos N.; Lamprianou, Iasonas; Andreou, Andreas S.; Pampaka, Maria (My University, 2005)
The Cultural Journeys in the Information Society is a dynamic hypermedia environment, which proposes the Electronic Roads as a meta-form for exploring cultural information that can form Cultural Journeys. The Electronic Roads meta-form facilitates travelers to explore the information space in a natural and continuous way similar to the exploration of physical roads. This meta-form is advantageous over existing cultural exploration approaches, which usually apply only to discrete information spaces, failing to provide users with continuous explorations and as a result users may lose their intended destinations. The proposed environment provides extendable cultural and historical content for three Mediterranean countries, i.e. Cyprus, Jordan and Egypt. Such a system could be ideal for teaching history and culture; therefore several Learning Activities have been developed in this context. The learning effectiveness of the environment was evaluated in primary schools in Cyprus, where pupils were asked to complete specific Learning Activities by either using the Cultural Journeys in the Information Society environment or a static hypermedia system. The results showed that the pupils found our environment to be easier to use, compared to the static system and that the performance of the pupils that used it was significantly higher. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Navigation; Cross-cultural projects; Interactive learning environments; Multimedia/hypermedia systems